Actual problems of atherosclerosis: point of view of clinician - R. S. Karpov (Бюллетень сибирской медицины, 2003)
In this lecture there is the information about historical steps of fundamental researches of pathogenesis of atherosclerosis, about biochemical, immunological and genetic abnormalities. Significance of x-ray, radionuclide methods in diagnosis of vascular affection is shown. The achievements of nowadays in the methods of treatment and prophylaxis of atherosclerosis are presented. Author’s own original synthetical classification of atherosclerosis is suggested.